Discovery of an Extensive Deep-Sea Fossil Serpulid Reef Associated With a Cold Seep, Santa Monica Basin, California - Georgieva, Magdalena N.; Paull, Charles K.; Little, Crispin T. S.; McGann, Mary; Sahy, Diana; Condon, Daniel; Lundsten, Lonny; Pewsey, Jack; Caress, David W.; Vrijenhoek, Robert C. (Frontiers in Marine Science, 2019)
Multibeam bathymetric mapping of the Santa Monica Basin in the eastern Pacific has revealed the existence of a number of elevated bathymetric features, or mounds, harboring cold seep communities. During 2013-2014, mounds at ~600 m water depth were observed for the first time and sampled by Monterey Bay Aquarium Research Institute’s ROV Doc Ricketts. Active cold seeps were found, but surprisingly one of these mounds was characterized by massive deposits composed of fossil serpulid worm tubes (Annelida: Serpulidae) exhibiting various states of mineralization by authigenic carbonate. No living serpulids with equivalent tube morphologies were found at the site; hence the mound was termed ‘Fossil Hill’. In the present study, the identity of the fossil serpulids and associated fossil community, the ages of fossils and authigenic carbonates, the formation of the fossil serpulid aggregation, and the geological structure of the mound are explored. Results indicate that the tubes were most likely made by a deep-sea serpulid lineage, with radiocarbon dating suggesting that they have a very recent origin during the Late Pleistocene, specifically to the Last Glacial Maximum ~20,000 years ago. Additional U-Th analyses of authigenic carbonates mostly corroborate the radiocarbon dates, and also indicate that seepage was occurring while the tubes were being formed. We also document similar, older deposits along the approximate trajectory of the San Pedro Basin Fault. We suggest that the serpulid tube facies formed in situ, and that the vast aggregation of these tubes at Fossil Hill is likely due to a combination of optimal physical environmental conditions and chemosynthetic production, which may have been particularly intense as a result of sea-level lowstand during the Last Glacial Maximum.